Fier By-Pass and its Role in the Socio-Economic Development of Fier Region - Ã‡inaj, Nevila; Dhimitri, Jostina (Mediterranean Journal of Social Sciences, 2013)
During the last decade, a growth has been noticed in the investments for the improvement and transformation of the roadinfrastructure. The realization of these investments according to the National Plan for Transportation is carried to support thesocio-economic developments in the country. The main purpose of this plan is the growth of the efficiency of the transportationsector, which supports and prompts the growth of the other sectors in economy. The far-reaching plans aim to make a betteruse of the farming & cattle growth, especially of the development of a decent sector for the economy, the services sector. Thissector is of a far greater importance when it comes to the tourism and its diversity in the country. Various studies have shownthat transportation infrastructure doesnâ€™t bring a new economic growth, but it simply pushes the redistribution of this growth thatwill happen somewhere else. This is the reason why the highways are designed for those areas where there is a potential foreconomic growth in the future. As a result, the truth is that the highway need is due to economic growth and not vice versa.Toverify this fact was considered the case of Fier By-pass, part of the north-south corridor (highway). Giving high consideration totime and space element, the working aims to show how this investment will affect the socio-economic development of the Fierregion. This analysis is also based on the weak socio-economic indexes of this region during the transition period. To draw theconclusions, the working project uses SOWT analysis. This shows briefly the advantages and disadvantages of Fieri By-passand what options and threats will be offered from this new transportation segment for Fieri region.